The Pattern of Folding in an Area of Migmatites between Neria and Qasigialik Fjords, South-West Greenland. - Kalsbeek, Feiko (Meddelelser om Grønland, 1967)
A geometrical analysis of mesoscopic structures (foliation planes, lineations, minor fold axes) in an area of migmatites is presented. In spite of the intensive migmatization of the rocks the observations fit into a more or less regular pattern, which is interpreted as the result of three superimposed folding phases, the first of which was roughly contemporaneous with an important phase of metamorphism and the second with the migmatization of the rocks in the area. For the interpretation of great circle diagrams use has been made of a computer program to find a great circle of best fit, the pole of which is used as the most plausible fold axis in a number of subareas.